Showing respect in school: what does it mean?. Issue 5 (3rd September 2018) - Goldson, D.
ABSTRACT: This article is a structured reflection on the notion of respect in school. It considers notions of respect, self-respect, ability, dependence, autonomy, compassion, and inequality, while at the same time analysing these fundamental notions through an institutional and sociological lens. The theoretical framework is due to Richard Sennett and the article makes a detailed application of Sennett's work to the institution of school. It is a case study that is focused on stimulating insight, reflection, and discussion within the teaching profession and its professional bodies.